Understanding the role of interpersonal violence in assisted partner notification for HIV: a mixed-methods study in refugee settlements in West Nile Uganda - Klabbers, Robin E.; Muwonge, Timothy R.; Ayikobua, Emmanuel; Izizinga, Diego; Bassett, Ingrid V.; Kambugu, Andrew; Tsai, Alexander C.; Ravicz, Miranda; Klabbers, Gonnie; O’Laughlin, Kelli N (Journal of global health, 2020)
Assisted partner notification (APN) for HIV was introduced in refugee settlements in West Nile Uganda in 2018 to facilitate testing of sexual partners. While APN is an effective strategy recommended by the World Health Organization, its safety has not been evaluated in a refugee settlement context in which participants have high prior exposure to interpersonal violence. The extent to which interpersonal violence influences APN utilization and the frequency with which post-APN interpersonal violence occurs remains unknown. Methods To explore the relationship between APN and interpersonal violence, a cross-sectional mixed-methods study was conducted at 11 health centers in or near refugee settlements serving refugee and national populations in West Nile Uganda. Routinely collected index client and sexual partner data were extracted from APN registers and semi-structured interviews were conducted with health workers. Results Through APN, 1126 partners of 882 distinct index clients were identified. For 8% (75/958) of partners, index clients reported a history of intimate partner violence (IPV). For 20% (226/1126) of partners, index clients were screened for post-APN IPV; 8 cases were reported of which 88% (7/8) concerned partners with whom index clients reported prior history of IPV. In qualitative interviews (N = 32), health workers reported HIV disclosure-related physical, sexual and psychological violence and deprivation or neglect. Incidents of disclosure-related violence against health workers and dependents of index clients were also reported. Fear of disclosure-related violence was identified as a major barrier to APN that prevents index clients from listing sexual partners. Conclusions Incidents of interpersonal violence have been reported following HIV-disclosure and fear of interpersonal violence strongly influences APN participation. Addressing HIV perception and stigma may contribute to APN uptake and program safety. Prospective research on interpersonal violence involving index clients and sexual partners in refugee settlements is needed to facilitate safe engagement in APN for this vulnerable population.
Keywords: Violence; HIV; Refugee settlements